Absolute and Relative Poverty Measurement : A Survey - Decerf, Benoit (World Bank, Washington, DC, 2022)
This paper reviews the debate opposing the absolute and relative approaches to monetary poverty measurement. The arguments for combining both approaches into a single “overall” monetary poverty measure are introduced. The most salient proposals of hybrid poverty lines are presented. Then, the reasons why specific poverty indices may be required when a hybrid line is used are discussed. The class of hierarchical poverty indices is described, focusing in particular on the hierarchical headcount ratio.